Current Antithrombotic Therapy Strategies in Children with a Focus on Off-Label Direct Oral Anticoagulants-A Narrative Review - Stefana Maria Moisa; Laura Mihaela Trandafir; Crischentian Brinza; Ingrith Crenguta Miron; Elena Tarca; Lacramioara Ionela Butnariu; Alexandru Burlacu (MDPI AG, 2022)
(1) Background: The incidence of thromboembolic events is relatively low in the general population, but it increases in hospitalized children and those who underwent thrombogenic procedures. Although the evidence regarding direct oral anticoagulants (DOACs) in children with venous thromboembolism (VTE) is growing, DOACs were excluded from existing guidelines due to the lack of reliable data at that moment. Therefore, current evidence on VTE management in children needs to be critically reviewed. (2) Methods: We have conducted a literature search in the Scopus, EMBASE, and MEDLINE databases using prespecified keywords to retrieve studies published between 2010 and 2022. (3) Results: Clinical trials highlighted that rivaroxaban and dabigatran had predictable pharmacokinetic and pharmacodynamic profiles in children, similar to those observed in adults. Dabigatran and rivaroxaban had a similar safety profile to standard therapy but improved thrombotic burden and resolution during follow-up. Most studies involving apixaban and edoxaban are ongoing, and results are awaited. (4) Conclusions: Dabigatran and rivaroxaban could be valid therapeutic options for VTE management in children. In the case of apixaban and edoxaban, results from ongoing clinical studies are required before using them in pediatric VTE.